Resting-state memory consolidation in Attention-Deficit/Hyperactivity Disorder - Bridget Scalia; Erin J. Wamsley (PLoS ONE, 2025)
This study examined declarative memory consolidation across a period of post-learning rest in individuals diagnosed with Attention-Deficit/Hyperactivity Disorder (ADHD). While eyes-closed waking rest after learning typically provides a memory benefit, we hypothesized that individuals diagnosed with ADHD would show reduced memory improvement after rest, compared to controls. N = 24 ADHD and N = 28 control participants listened to a short story followed by either 15 min of rest or a 15 min distractor task (within-subjects). A recall test was administered immediately afterwards and 24hrs later. EEG (electroencephalography) was recorded during the rest period, along with EOG (electrooculography) and EMG (electromyography). While ADHD and control groups differed substantially in resting-state mental and neural activity, the effect of rest on memory consolidation did not differ between groups. However, in exploratory analyses controlling for inattention symptoms, rest impaired memory in participants with ADHD, while improving memory in controls. These observations add to a growing literature describing how persons with ADHD differ from controls in resting state brain and mental activity.